The influence of transformational leadership and motivation on employee performance in the F&B Department at the Grand Mercure Hotel Medan - Griche Tambunan, Sontina (Trigin Publisher, 2025)
This study aims to analyze the influence of transformational leadership and motivation on employee performance in the Food & Beverage (F&B) Department at the Grand Mercure Medan Hotel. This study uses a quantitative approach with a survey method, where data are collected through questionnaires to 28 respondents consisting of F&B Department employees. The data analysis technique uses multiple linear regression to test the partial and simultaneous effects of both independent variables on the dependent variable. The results of the partial test indicate that transformational leadership has a positive and significant effect on employee performance, while motivation does not show a partially significant effect. However, simultaneously both have a significant effect on performance, as proven by the F test. The coefficient of determination (R²) of 0.496 indicates that 49.6% of the variation in employee performance can be explained by transformational leadership and motivation. This finding confirms the importance of the role of inspirational leadership and attention to employee needs in creating optimal work performance. Although motivation is not dominant individually, its existence remains an important component in the collective performance prediction model. This study recommends that hotel management strengthen transformational-based leadership training and formulate motivational strategies that are more adaptive to the characteristics of the younger generation that dominates the workforce.